Evaluation of Antibacterial Potential of Lime (Citrus aurantiifolia) Peel Extract Cream againts Staphylococcus epidermidis - Go, Stephannie Felicia; Pakan, Prisca Deviani; Ratu, Kristian; Riwu, Magdarita (Cendana Medical Journal, 2024)
Background: Acne vulgaris is a common chronic skin disease. Staphylococcus epidermidis is a bacterium commonly found in acne lesions. The increased and irrational use of antibiotics can result in antibiotic resistance. One part of the plant that can be utilized is lime (Citrus aurantiifolia) peel. In its application, lime peel extract requires a drug preparation form that can provide optimal effects on the skin, such as a cream. Objectives: To determine the antibacterial potential of lime (Citrus aurantiifolia) peel extract cream against Staphylococcus epidermidis. Methods: This study was a true experimental type with a Post-Test Only Control Group Design. This research consisted of treatment groups given lime peel extract cream at concentrations of 10%, 25%, 50%, 75%, negative control group, and positive control group. The antibacterial test method was performed using disc diffusion method. One-way ANOVA test was used for analysis. Results: Lime peel extract cream has antibacterial potential against Staphylococcus epidermidis bacteria with a resulting inhibition zone at a concentration of 75% is strong, while other concentrations did not produce any inhibition zones. Conclusion: Lime (Citrus aurantiifolia) peel extract formulation in cream preparation has antibacterial activity against Staphylococcus epidermidis.